Enhanced pyroelectric and piezoelectric properties of PVDF – BaTiO3 nanocomposites layered samples. (26th October 2019) - Singh, Pramod Kumar; Gaur, Mulayam Singh; Johari, Dilip; Sagar, Rohan; Gupta, Akash; Sharma, Ashutosh; Singh, Govind; Yadav, Mayank
Abstract: The triple-layered polyvinylidene fluoride (PVDF) and barium titanate (BaTiO3 ) nanocomposites were prepared using sol-gel method. The structure of polymer is often complex after introducing the nanoparticles. Such properties of BaTiO3 nanoparticle filled PVDF nanocomposites have been investigated by X-ray diffraction and Fourier-transform infrared (FTIR) spectroscopy. XRD and FTIR result indicate the significant improvement in structural morphology of triple layered polymer nanocomposite. Pyro and piezoelectric result also shows the improvement in pyroelectric and piezoelectric coefficients, which is due to enhancement of β-phase.